Effects of marine-derived n-3 PUFA supplementation on soluble adhesion molecules: A systematic review and dose-response meta-analysis of randomized controlled trials - Mahsa Shirani; Shokoofeh Talebi; Omid Sadeghi; Shirin Hassanizadeh; Gholamreza Askari; Mohammad Bagherniya; Amirhossein Sahebkar (Elsevier, 2023)
Long-chain n-3 poly unsaturated fatty acids have anti-inflammatory effects but their effects on serum levels of adhesion molecules are inconsistent and contradictory. In this updated systematic review and meta-analysis, marine sources of omega-3 fatty acids were pooled up to determine the effects of omega-3 supplementation on adhesion molecules. PubMed-Medline, SCOPUS, Web of Science and Google Scholar databases (from inception to April 2023) were searched and all RCTs investigating the effects of marine sources of omega-3, on blood concentrations of adhesion molecules were included and a meta-analysis undertaken. Forty-two RCTs were included involving 3555 participants aged from 18 to 75 years. Meta-analysis of 38 arms from 30 RCTs reporting serum concentrations of vascular cell adhesion molecule-1 (VCAM-1) showed a significant reduction after omega-3 supplementation (WMD: −1.26, 95% CI: −1.88 to −0.64 ng/mL, P < 0.001). Meta-analysis of 40 arms from 30 RCTs reporting serum concentrations of intercellular adhesion molecule-1 (ICAM-1) revealed a reduction following omega-3 supplementation, although it was not significant (WMD: −1.76, 95%CI: −3.68 to 0.16 ng/mL, P = 0.07). Meta-analysis of 27 arms from 21 trials showed no effect on E-selectin (WMD: 0.01, 95%CI: −0.02 to 0.04 ng/mL, P = 0.62). Pooling 15 arms from 11 RCTs showed a marginally significant reducing effect on P-selectin concentrations (WMD: −2.67, 95%CI: −5.53 to 0.19 ng/mL, P = 0.06). A considerable decrease in VCAM concentration was observed after omega-3 supplementation in this meta-analysis with a trend to decreases in both ICAM and P-selectin levels, with effects that may be significant depending on study design, and there was no effect on E-selectin.